Figures 2-12 from: Henry T (2012) Revision of the Plant Bug Genus Tytthus (Hemiptera, Heteroptera, Miridae, Phylinae). ZooKeys 220: 1-114. https://doi.org/10.3897/zookeys.220.2178 - Henry, Thomas (Zenodo, 2012)
Figures 2-12 - Tytthus spp. 2 Tytthus alboornatus, macropterous ♂ (holotype: USA, Jacksonville, Florida, 23 July 1926, E. D. Ball, USNM) 3 Tytthus alboornatus, macropterous ♀ (USA, South Carolina, Colleton Co., 1.1 km W of Bennetts Point, 3 May 2003, A. G. Wheeler, Jr., USNM) 4 Tytthus alboornatus, brachypterous ♀ (USA, South Carolina, Colleton Co., Bear Island Wildlife Management Area, 3 May 2003, A. G. Wheeler, Jr., USNM) 5 Tytthus amazonicus, macropterous ♂ (Brazil, Amazonas, Reserva Ducke, 25 km NNE of Manaus, 26 July 1973, R. T. Schuh, AMNH) 6 Tytthus amazonicus, macropterous ♀ (Brazil, Amazonas, Reserva Ducke, 25 km NNE of Manaus, 26 July 1973, R. T. Schuh, AMNH) 7 Tytthus balli, macropterous ♂ (USA, Texas, Refugio Co., 6 mi. N Bayside, 20 Apr. 1983, T. J. Henry & A. G. Wheeler, Jr., USNM) 8 Tytthus balli, brachypterous ♀ (USA, Florida, Jacksonville, 23 July 1926, E. D. Ball, USNM) 9 Tytthus chinensis, macropterous ♂ (Guam, Asan Village, Asan River at Rt. 1, 8 June 2008, R. S. Zack, USNM) 10 Tytthus chinensis, macropterous ♀ (Guam, Asan Village, Asan River at Rt. 1, 8 June 2008, R. S. Zack, USNM) 11 Tytthus columbiensis, macropterous ♂ (holotype: Colombia, Valle de l Cauca, Palmira, 25 Oct. 1958, G. Bravo, USNM) 12 Tytthus entrerianus, macropterous ♂ (paratype: Argentina: Entre Rios, Concordia, Apr. 1939, L Carpintero, USNM).